Industrial revolution 4.0: Towards a conceptual framework on the implementation challenges in Malaysian manufacturing sector - Lee, Eng Keong; Yacob, Peter; Yusof, Cik Hayati; Nadarajan, Premkumar (2017)
The fourth industrial revolution, also called Industry 4.0 (I4.0) involves digitization of the manufacturing sector, with sensors (chips) in virtually all product components and manufacturing equipment, widespread cyber physical systems (CPS), and analysis of all relevant data. Industry 4.0 influences essential applications in manufacturing processes, the transformation is to be far-reaching but the pace of change to be slower than in the digital disruption of the consumer Internet.Due to long investment cycles, companies tend to be cautious in their decision making when it comes to significant disruptions. With expected Investments of US$ 907B by 2020, the world is definitely moving toward a new industrial phase, but are the Malaysian Manufacturing Companies ready for it? The aim of the study is to propose a conceptual study investigating the association of three challenges which consists of unqualified employees, high costs, vague return on investment are challenges towards Industry 4.0 revolution in Malaysian manufacturing sector.The novelty of the proposed conceptual framework shall increase the understanding that manufacturing sector should act along three challenges to overcome the implementation changes towards embracing Industry 4.0; which drives the next level of operational effectiveness, adapt business models to capture shifting value pools, and build the foundations for digital transformation.